2012
DOI: 10.1111/j.1541-4337.2012.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the High‐Pressure Processing of Meat and Meat Products

Abstract: For years, high-pressure processing has been viewed as useful for pasteurizing food while maintaining the quality of fresh food. However, even at moderate pressure, this process is not without effects on food, especially on meat products. These effects are especially important because pressure greater than 400 MPa is generally necessary to achieve efficient microbial inactivation. In this review, recent advances in the understanding of the impacts of high pressure on the overall quality of raw and processed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(116 citation statements)
references
References 205 publications
(403 reference statements)
1
106
2
7
Order By: Relevance
“…What is not less important, other authors mention that the microbial count is not reduced to the final effect immediately after the pressure treatment but shows a significant decrease during cold storage (Jofré et al, 2009;Simonin, Duranton, & de Lamballerie, 2012). Analysing the information in scientific literature and experiments data, it can be concluded that the prior amount of microorganisms (contamination level) play very significant role in the meat, and the stages of microorganism development were important.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…What is not less important, other authors mention that the microbial count is not reduced to the final effect immediately after the pressure treatment but shows a significant decrease during cold storage (Jofré et al, 2009;Simonin, Duranton, & de Lamballerie, 2012). Analysing the information in scientific literature and experiments data, it can be concluded that the prior amount of microorganisms (contamination level) play very significant role in the meat, and the stages of microorganism development were important.…”
Section: Resultsmentioning
confidence: 98%
“…The basic principles that determine the behaviour of foods during HPP technology are Le Chatelier's principle, principle of microscopic ordering, and isostatic principle (Yordanov & Angelova, 2010). The isostatic transmission of pressure provides the instantaneous treatment to the processed product with no gradient, resulting in the uniform pressure distribution irrespective of the size and geometry of the material; moreover, food can be processed at ambient or even lower temperatures (Simonin, Duranton, & de Lamballerie, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…High Pressure Processing (HPP) is an effective nonthermal means to improve food safety and shelf-life, and is increasingly being used as a post-process intervention for meat products (Simonin et al, 2012;Campus, 2010;Garriga and Aymerich, 2009). HPP subjects food to an elevated pressure of 100e1000 MPa typically at temperatures below 60 C. The mechanism by which HPP inactivates foodborne pathogens include: 1) cell membrane alterations, a major factor to cause death (Moussa et al, 2009); 2) ribosome dissociation, to limit cell viability (Abe, 2007); and 3) cell structure damage or destruction (Hsu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…High hydrostatic pressure (HHP) represents an innovative alternative approach likely to be used to offset reduction of preservatives. It enables inactivation of foodborne pathogens and spoilage microorganisms while limiting detrimental effects on nutritional and organoleptic qualities of food (Hayman et al, 2004;Patterson, 2005;Simonin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%